PENGARUH LOCUS OF CONTROL, LOVE OF MONEY, DAN GENDER TERHADAP PERSEPSI MAHASISWA MENGENAI ETIKA PROFESI AKUNTAN - Ega Briantono; Tarmizi Achmad (Diponegoro Journal of Accounting, 2020)
The objective of this research is to examine the influence of locus of control, love of money, and gender on students’ perception of professional accounting ethics. Samples whose data are used in this study were obtained using pusposive sampling method with the criteria determined were respondents have taken the Business Ethics course. The sample obtained were undergraduate Accounting students of Diponegoro University and Semarang State University, totaled 77 people. The data were analyzed with descriptive statistics and classical assumption test. The hypothesis is tested using regression. That processes were assisted with IBM SPSS Statistics 21 computer software. The empirical results of this study indicate that external locus of control have negatively influenced the students’ perception of professional accounting ethics, love of money have positively influenced the students’ perception of professional accounting ethics, and gender orientation haven’t significantly influenced the students’ perception of professional accounting ethics.